Quantitative analysis of Latin American and Caribbean journals indexed in Web of Science (2021) - Marín-Velásquez, Tomás Darío (Revista General de Información y Documentación, 2022)
This paper presents a quantitative study of Latin American journals indexed in the Web of Science for 2021. The main objective is to quantitatively analyze the visibility and impact of journals published in the region, included in the Web of Science cores. A meta-analytical approach methodology was applied with data obtained from the official Web of Science portal. The data were processed using multivariate statistics and the results were analyzed through graphs and classification of countries by number of journals and impact factor with a classification-regression tree. The results indicated that 6 countries group 88.64% of indexed journals: Brazil, Colombia, Argentina, Mexico, Chile and Venezuela. The core with the largest number of journals is ESCI with 60.28% of the total, with Colombia being the country with the highest percentage with respect to its total with 80.0%.  The countries with journals with JCI impact factors higher than the average of their categories (JCI > 1) were Brazil, Chile, Colombia, Mexico and Venezuela. The countries are classified in 8 groups, with Argentina, Brazil and Colombia as the most important. The language of greatest use is Spanish with 34.2% of the journals, followed by English and Portuguese. It is concluded that, in the region there is a low number of journals indexed in Web of Science and from few countries, so it is necessary to promote the indexing of journals by increasing their quality and placing them in the main cores so that more countries increase their presence in the database.
Keywords: Visibility; Impact factor; Latin America; Web of Science; Journals